Design Study of Gas Cooled Fast Reactor (GFR) with Uranium Plutonium Carbide (UC-PuC) as Fuel with Addition Protactinium (Pa-231) - Sabrina, Alvi Nur; Sari, Arindi Kumala; Janah, Laela Nur; Maulana, M. Rizqi (Computational And Experimental Research In Materials And Renewable Energy, 2020)
Analysis performance of uranium plutonium carbide (UC-PuC) as fuel in gas cooled fast reactor (GFR) with addition of protactinium as a burnable poisons has been done. Neutronic analysis in this research was carried out using the SRAC code from JAERI with a nuclear library based on JENDL 4.0. The calculation is carried out by two steps, the first step is the PIJ calculation which calculates the fuel cell and the second step is the CITATION calculation which calculates the various configurations of the reactor core. The first calculation determines the k-eff value in a homogeneous core configuration. The results obtained show that the percentage of 10% is the sloping result with a k-eff value of 1%. The second calculation determines the k-eff value in the heterogeneous core configuration. The results obtained indicate that the fuel variation 8% -10% -12% is the most critical percentage with a peak power density value of less than 100 Watt/cc. Furthermore, the addition of protactinium with a variation of 0% to 5%. At a protactinium 4% percentage and 63% fuel fraction, the excess reactivity value is 1.02% or close to 1% which indicates that the reactor is in a critical condition.